Populations and climatic evolution in North Tropical Africa from the end of the Neolithic to the dawn of the modern Era - (:unkn) unknown (My University, 2015)
At the end of the Neolithic Era, during the third millennium BCE, there were fewer humid periods, and the sub-Saharan and Sahelian zones from the Atlantic to Lake Chad assumed their current geographical form. Since then, the climate has continued undergoing major variations. The succession of climatic episodes, humid or dry, is pointed out along with the episodes'complex interactions. These variations are placed in parallel to cultural phases of evolution in archaeology and history. Climate-related events have always had heavy consequences on the peopling of this vast region, often subject to extreme natural conditions. The relative synchronism between the principal cultural trends from west to east across the Sahel seems to have often been subject to swings in the climate and the resulting environmental changes.
Keywords: African Research